Vestibularmigraine-A Challenging Clinical Entity Rhinoscleroma-A Rare Granulomatous Disease in a Child - Santosh Kumar Swain1 , Priyanka Debta2 , Smarita Lenka3 , Smrutipragnya Samal3 , Anurag Dani4 , Soma (Institute of Medico-legal Publications Pvt Ltd, 2020)
Vestibular migraine (VM) is a distinct clinical entity which accounts for major vestibular symptomsamong the adult and children. It is presently thought of as a major etiology for episodic dizziness. Thepathophysiology for VM is not completely understood and is always a puzzling dilemma. Patients oftenpresent with vertigo, headache, photophobia, and phonophobia. The clinical examinations and laboratoryinvestigations are usually within normal limits. The diagnosis of VM is often challenging as there are noconfirmatory tests available. The treatment is often similar to the migraine headache. The present-daymanagement is to take the similar prophylactic medications needed for migraines such as beta-blockers,antidepressants, and anticonvulsants drugs. It is always a challenging disease for clinicians and often createsa puzzle for diagnosis and treatment. Accurate management of VM needs a proper understanding of thepresent literature which are discussed details in this review article.